Exemplary practices in field trips to natural environments. Issue 4 (16th January 2014) - Tal, Tali; Lavie Alon, Nirit; Morag, Orly
Abstract: In light of the literature that deals with challenges of outdoor education, this paper presents exemplary practices in field trips to natural environments. We offer an analysis of 62 field trips of students in grades 4–8 (age 10–14), guided by professional guides or by teachers. In aiming at elucidating the qualities of exemplary fieldtrips, we analyze five examples of high quality field trips. Each of the five was exemplary in several aspects, but not necessarily in all. Data were collected though observations and interviews with teachers, guides and students. Interpretative analysis was used in addition to an analytic framework that we developed previously. In general, we stress that good collaboration between the guide and the teacher, who enact active learning and psychomotor activity, and make much use of the environment for student exploration and interaction, are the key to high quality outdoor learning experiences. We provide several examples to support this claim. Other aspects we highlight are a sense of freedom, time and opportunity to enjoy nature and the opportunities to have meaningful social interactions. In light of the prevalent critique toward current outdoor education practice, we suggest the research community learn from good practices. © 2014 Wiley Periodicals, Inc. J Res Sci Teach 51: 430–461, 2014